Assessing the Effects of Short-Term Culture and Language Immersion Program: A Hong Kong Case - Bertha Du-Babcock (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2016)
The current study examines the effects of a four-week short-term culture and language immersion program. The Program involves four key curricular components and covered three phases: the pre-trip planning and preparations, implementation of the Program, and the post-trip debriefings.  Data were collected prior to, during, and after the students’ taking their four-week immersion program. A 360-degree assessment of the Program was employed to evaluate its effectiveness. The assessment involves triangulation of quantitative and qualitative data.  Two statistical measurements (Analysis and Variance and Pearson Correlation Coefficient tests) were employed to assess the Program effectiveness.  The results show that the for-week short-term culture and language immersion program achieved all its learning objectives.  By all measures, the students experienced increased confidence in using English, demonstrated a greater awareness of culture, were able to identify and explain cultural differences between Hong Kong and the host culture, and learned to apply language learning strategies and to begin to develop intercultural communication skills.